2002
DOI: 10.1152/advan.00039.2002
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Pathophysiology and Treatment of Spinal Cord Injury

Abstract: Thirty years ago, patients with spinal cord injury (SCI) and their families were told "nothing can be done" to improve function. Since the SCI patient population is reaching normal life expectancy through better health care, it has become an obviously worthwhile enterprise to devote considerable research effort to SCI. Targets for intervention in SCI toward improved function have been identified using basic research approaches and can be simplified into a list: (1) reduction of edema and free-radical productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
221
0
27

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(249 citation statements)
references
References 136 publications
1
221
0
27
Order By: Relevance
“…Methods that target incremental augmentation of neuroplastic processes are emerging using technologies that upregulate neurotransmitter systems, 30 increase neurite growth, 14,31 or seek to replace lost neurons through genetic manipulation 32 or neural implantation. 13 Changes induced in motor control by each of these intervention technologies are likely to be modest and incremental, therefore requiring sensitive, objective measurement of effects to reach general application individually and in concert.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods that target incremental augmentation of neuroplastic processes are emerging using technologies that upregulate neurotransmitter systems, 30 increase neurite growth, 14,31 or seek to replace lost neurons through genetic manipulation 32 or neural implantation. 13 Changes induced in motor control by each of these intervention technologies are likely to be modest and incremental, therefore requiring sensitive, objective measurement of effects to reach general application individually and in concert.…”
Section: Discussionmentioning
confidence: 99%
“…9 The promise of new treatment approaches and their likely incremental effects on voluntary control demands objective measures with greater sensitivity be employed to assess their effectiveness. The attempted therapeutic manipulation of neuroplasticity [10][11][12] to modify neural circuitry through neural implantation 13 and molecular manipulation of surviving neural structures 14 will require objective quantification methods to reach clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro studies have shown that ischemia of neuronal tissues activates NMDA receptors and glutamate released to the media at increasing concentrations. 19 Different models of spinal trauma have shown that glutamate receptor antagonists have therapeutic effects in both structural and functional recovery. The non-competitive NMDA ion-channel blocker MK-801 and blockade of the non-NMDA ionotropic receptors with AMPA/kainate receptor antagonist 1,2,3,4-tetrahydro-6-nitro-2,3-dioxobenzol[f]quinoxaline-7-sulfonamide disodium have both demonstrated significant improvements in trauma models.…”
Section: Parameters Of Oxidative Stressmentioning
confidence: 99%
“…A quebra da barreira hematoespinal desencadeia aumento da permeabilidade vascular, com formação de edema, início da resposta infl amatória, perda de cargas aniônicas e extravasamento de proteínas plasmáticas (ROWLAND et al, 2008). Concomitantemente, a ruptura da microvasculatura gera hemorragia que, associada ao edema, leva à isquemia medular, estendendo-se rostral e caudalmente (HULSEBOSCH, 2002;ROWLAND et al, 2008). Além disso, células gliais e endoteliais liberam substâncias vasoativas que se concentram próximo à lesão, contribuindo para a isquemia neuronal (GRILL, 2005).…”
Section: Fisiopatologia Do Trauma Medular a Lesãounclassified
“…Ela causa desequilíbrio eletrolítico signifi cativo (KWON et al, 2004;SEVERO et al, 2007), resultante da liberação excessiva e recaptação inadequada do glutamato (LEPORE et al, 2011), com consequente transmissão sináptica excitatória prolongada (HULSEBOSCH, 2002;ROWLAND et al, 2008). Isso acarreta o infl uxo acentuado de sódio e Ca 2+ pela ativação de receptores ionotrópicos e metabotrópicos, além da entrada do Ca 2+ pelos CCDV, abertos com a despolarização da membrana (BERRIDGE, 2002).…”
Section: Fisiopatologia Do Trauma Medular a Lesãounclassified